Effectiveness and efficiency of primary care based case management for chronic diseases: rationale and design of a systematic review and meta-analysis of randomized and non-randomized trials [CRD32009100316] - Freund, Tobias; Kayling, Felizitas; Miksch, Antje; Szecsenyi, Joachim; Wensing, Michel (BMC health services research, 2010)
Case management is an important component of structured and evidence-based primary care for chronically ill patients. Its effectiveness and efficiency has been evaluated in numerous clinical trials. This protocol describes aims and methods of a systematic review of research on the effectiveness and efficiency of case management in primary care.
Gesehen am 04.12.2023